2018
DOI: 10.1542/peds.2017-2876
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Psychological Screening Into Medical Care for Youth With Abdominal Pain

Abstract: Systematic screening for anxiety, pain, and pain-related disability as a routine part of medical care can be reliably implemented with clinically meaningful results. Future directions include examining the role of anxiety over the long-term and reducing clinician burden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(48 citation statements)
references
References 40 publications
4
44
0
Order By: Relevance
“…Clinical data were gathered from 56 children between the ages of 9-14 with FAPD from a large Midwestern children's hospital using de-identified data as a part of an Institutional Review Board approved process. These youth were also involved in prior studies examining (1) clinical characteristics of youth with FAPD [7][8][9], (2) neuroimaging of pain, or (3) behavioral interventions for FAPD [14,15]. The participant's gastroenterologist confirmed that the patient met criteria for FAPD based on ROME IV guidelines and also performed an FC assay.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Clinical data were gathered from 56 children between the ages of 9-14 with FAPD from a large Midwestern children's hospital using de-identified data as a part of an Institutional Review Board approved process. These youth were also involved in prior studies examining (1) clinical characteristics of youth with FAPD [7][8][9], (2) neuroimaging of pain, or (3) behavioral interventions for FAPD [14,15]. The participant's gastroenterologist confirmed that the patient met criteria for FAPD based on ROME IV guidelines and also performed an FC assay.…”
Section: Methodsmentioning
confidence: 99%
“…Participants were stratified into risk groups (range: 0-3) based on their scores on the measures detailed below. These measures were administered as part of their clinical care to determine risk status [7,15]. Clinical elevations in all three domains listed below were defined as the most clinically complex FAPD group.…”
Section: Clinical Riskmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the associations between GI distress and anxiety, routine screening for anxiety symptoms within all GI distress presentations by pediatricians, teachers, school nurses, and other child-facing professionals could likely help to increase appropriate referrals (Cunningham et al, 2018). However, because these individuals at initial access points for youth mental healthcare do not always have training, resources, or time to administer such mental health evaluations, using GI symptoms to assess psychopathologcal risks may be useful as a preliminary step.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it is possible to compare rates of telehealth use among providers within a group to assess whether adoption has been embraced by providers equally, as well as rates of provider appointment slot utilization and patient no-shows. Within the chronic pain literature, screening tools within EHR have been successfully implemented to identify patients with anxiety and functional disability among youth with abdominal pain [ 18 ]. This approach to screening has multiple implications for use with telehealth, including screening for patient appropriateness for telehealth-delivered chronic pain treatment.…”
Section: Introductionmentioning
confidence: 99%